An Experimental Study on Fibre Reinforced Geopolymer Concrete Composites- Glass Fibre, Copper Slag - Asanammal Saral, J; Gayathri, S; Tamilselvi, M; Raghul Raj, B (International Journal of Engineering and Technology, 2018)
The major problem of the world is facing today is environmental pollution. It is well known that for the production of 1-ton of cement consumes more energy and exhibit 0.8-ton of CO2 .On the other hand Fly ash is a residue from the combustion of pulverized coal from the flue gases of thermal power plant. Recently, the fly ash is not effectively used and a large part of it is disposed in landfill. Due to this problem the various researchers have sort for a new binder to minimize the consumption of OPC. This study evaluates the strength of geopolymer concrete having fly ash as the major binding material and the sand a fine aggregate was replaced with copper slag of 40%Â  and glass fiber to enhance the mechanical properties have been presented. This paper analyses on the mechanical properties of eopolymer concrete composites such as compressive strength, split tensile strength and water absorption in heat curing at 60ËšC for 24 hrs in hot air oven. Glass fibers were added in the mix in the volume fraction of 0.5%, 1.0%, 1.5% and 2.0% volume of the concrete. The influence of fiber content in terms of volume fraction on the compressive, split tensile strength of geopolymer concrete is presented. The result shows the elevated performance of the properties exhibited by the geopolymeric concrete with and without fibres.